IMPLEMENTASI MODEL PEMBELAJARAN HYBRID TEACHING GAMES FOR UNDERSTANDING DAN SPORT EDUCATION MODEL TERHADAP MOTIVASI BELAJAR PJOK - Anugrah, Dhaniel Wahyu Putra (Universitas Syiah Kuala, 2023)
Motivation is the impulse that arises from oneself to make a good change in action. There are 5 types of motivation, namely Instrinsic Motivation, Identified Regulation, Introjected Regulation, External Regulation, and Amotivation. Currently, there are still many students who have poor learning motivation. Therefore, hybrid learning is conducted to improve students' learning motivation by combining TGfU and SEM learning models. Abroad, many studies have been conducted on the hybrid learning model of TGfU and SEM. However, in Indonesia it is still rare to conduct research between these learning models. So this research was conducted to find out how the effect of TGfU and SEM hybrid learning models on PJOK learning motivation. The method used is quantitative method. The number of samples was 70 students divided into control groups and experimental groups.The results of the study in the control group showed that the sig-2 tailed value 0.05, namely intrinsic motivation, introjected regulation, external regulation, and amotivation which means there is no difference and one type has a sig-2 tailed value 0.05, namely identified regulation which means it has a difference. While in the experimental group all types of motivation have a sig-2 tailed value 0.05 which means there is a difference. The conclusion of this study is that the TGfU-SEM hybrid model has an influence on the learning motivation of PJOK students.Keywords: hybrid; TGfU-SEM; motivation; physical education